Front Cover: Zinc‐Catalyzed Esterification of N‐β‐Hydroxyethylamides: Removal of Directing Groups under Mild Conditions (Eur. J. Org. Chem. 34/2017). Issue 34 (24th August 2017) - Nishii, Yuji; Hirai, Takahiro; Fernandez, Sarah; Knochel, Paul; Mashima, Kazushi
Abstract : The Front Cover shows a trick for the facile cleavage of amide C–N linkages. The Zn(OTf)2 ‐catalyzed esterification of amides (alcoholysis) is achieved with the assistance of an intramolecular acyl rearrangement process. The N ‐β‐hydroxyethyl group, a key functional group for the present esterification system, can be readily installed to various secondary amides by treatment with an epoxide; accordingly, a one‐pot removal of several amide‐based directing groups is realized under mild reaction conditions. More information can be found in theCommunication by K. Mashima et al.